A Structural Equation Modelling Approach to the Examination of Bank Customers’ Behavioral Intention Antecedents to Adopt Internet Banking in Kurdistan - sabir, Bawan Y.; Aziz, Hassan M.; Hasan, Kovan O.; Abdulrahman , Karwan I.; Aziz , Azhy A.; Ali , Barzan O.; Gardi, Bayar (Polytechnic Journal of Humanities and Social Sciences, 2024)
Abstract—The study aims to determine and test the significance of specific behavioral antecedents influencing the adoption of internet banking by bank customers in Erbil, Kurdistan. The study focuses on studying the behavioral antecedents of bank customers of the top-three 2021 banks ranked best in terms of banking services in Erbil, Kurdistan. As a result, 283 questionnaire responses collected from bank customers were used in modelling a structural equation model essential for analyzing the structural influence of each behavioral antecedent on the adoption of internet banking. The results of the study revealed that the adoption of internet banking products and services in Kurdistan is mainly shaped around security and reliability, bank customers’ trust, habits and attitudes, facilitating conditions, effort expectancy and performance expectancy behavioral antecedents. The effects of perceived website usability, hedonic motivation and social influence on the adoption of internet banking were observed as insignificantly positive. Practically, the implications demand that bank managers engage in a major innovative drive aimed at improving internet banking features, usability, performance, reliability and security. The study’s contributions direct policymakers and bankers into structuring internet banking products and services to specifically meet bank customers in Kurdistan’s needs, wants and preferences. On a theoretical level, the study advances propositions, implications and testing of the UTAUT, whose application in Kurdistan is academically sidelined. Keywords: Adoption, behavioral intentions, internet banking, structural equation modelling